2021
DOI: 10.1080/0886022x.2021.1939049
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital acute kidney injury and atrial fibrillation: incidence, risk factors, and outcome

Abstract: Background: The incidence and the risk factors of in-hospitalized acute kidney injury (AKI) in patients hospitalized for atrial fibrillation (AF) were unclear. Methods: The Improving Care for Cardiovascular Disease in China-AF (CCC-AF) project is an ongoing registry and quality improvement project, with 240 hospitals recruited across China. We selected 4527 patients hospitalized for AF registered in the CCC-AF from January 2015 to January 2019. Patients were divided into the AKI and non-AKI groups according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…However, after adjustment only atrial fibrillation was independently associated with the development AKI in patients undergoing CS (OR: 3.11, 95% CI:1.08-9.40, p=0.037). In concordance with this finding, Wang et al reported that the risk of inhospital AKI increased significantly in patients hospitalized for atrial fibrillation [19]. Furthermore, the presence of risk factors for atrial fibrillation often coexists and may predispose to the development of kidney disease and vice versa.…”
Section: Discussionmentioning
confidence: 64%
“…However, after adjustment only atrial fibrillation was independently associated with the development AKI in patients undergoing CS (OR: 3.11, 95% CI:1.08-9.40, p=0.037). In concordance with this finding, Wang et al reported that the risk of inhospital AKI increased significantly in patients hospitalized for atrial fibrillation [19]. Furthermore, the presence of risk factors for atrial fibrillation often coexists and may predispose to the development of kidney disease and vice versa.…”
Section: Discussionmentioning
confidence: 64%
“…However, after adjustment, only atrial fibrillation was independently associated with the development AKI in patients undergoing CS (OR: 3.11, 95% CI: 1.08-9.40, p = 0.037). In concordance with this finding, Wang et al reported that the risk of in-hospital AKI increased significantly in patients hospitalized due to atrial fibrillation [19]. Furthermore, the presence of risk factors for atrial fibrillation often coexists with and may predispose to the development of kidney disease, and vice versa.…”
Section: Discussionmentioning
confidence: 66%
“…We showed similar prediction accuracy for these parameters in the ROC curve analysis. Wang et al recruited 4527 patients hospitalized for atrial fibrillation and found that the incidence of in-hospital AKI in patients with atrial fibrillation was 2.6 times higher than that in patients with sinus rhythm [38]. Atrial fibrillation is considered to be related to adverse renal outcomes and causes AKI by several mechanisms such as hemodynamic perturbations and renal ischaemia from an embolic event [39,40].…”
Section: Discussionmentioning
confidence: 99%